ANALISIS TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS UNTUK MEMBAYAR PAJAK - Rahayu Utami; Muzakir Muzakir (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
This study aims to analyze how the influence of the tax payer consciousness, knowledge and understanding of tax laws, good perception on the effectiveness of the tax system, and the level of confidence in the government and legal system of the willingness to pay taxes on KPP Kalideres in West Jakarta . Is there a significant and positive effect, or no effect of this study make a previous study as one of the sources of literature and references, but this study has some differences with previous studies. The difference include : population, place, variables, data processing methods, as well as the number of samples used This study uses four independent variables including: (1) Paying taxes consciusness. (2) Knowledge and understanding system of taxtion, indicator: the desire of taxpayers to understand the system perpajkan. (3) a good perception on the effectiveness of the system of taxation. (4) The level of trust in the system of government and law. And the dependent variable is the willingness to pay taxes.